IMPLEMENTASI PERMENDIKBUD NO. 23 TAHUN 2015 TENTANG PENUMBUHAN BUDI PEKERTI - Anis Kurnia; Irawan Suntoro; Hermi Yanzi (FKIP Unila, 2017)
This research was conducted to describe the Implementation of Education and Culture Ministry No. 23 Year 2015 about the Development of Characteristics Education in SMAN 2 Bandar Lampung. Spesifically for describing characteristics aspect which will be expanding, a program/ activity to improve the characteristics and teachers role in creating students characteristics. The method used here is qualitative-descriptive, the research subjects are the second grade students, teachers, educational staffs, and school minister. The data collecting techniques are interview, observation, and documentation. The result of this research is that the Implementation of Education and Culture Ministry No. 23 Year 2015 has been running and appropriate with instruction. This result is proved by the existing of habitual aspects which improve characteristics, and some activities/programs that improve characteristics, one of those activities is Jumat Ceria (Cheerful Friday), along with teachers contribution has been seen from what the teachers have done.Penelitian ini bertujuan untuk mendeskripsikan Implementasi Permendikbud No. 23 Tahun 2015 Tentang Penumbuhan Budi Pekerti di SMA Negeri 2 Bandar Lampung. Secara khusus untuk mendeskripsikan aspek budi pekerti yang ditumbuhkembangkan, program/ kegiatan menumbuhkan budi pekerti dan peran guru dalam menumbuhkan budi pekerti. Metode yang digunakan yaitu deskriptif kualitatif, subjek yang diteliti merupakan siswa kelas XI, guru, tenaga kependidikan, dan kepala sekolah. Teknik pengumpulan data adalah wawancara, observasi, dan dokumentasi. Hasil penelitian ini adalah Implementasi Permendikbud No. 23 Tahun 2015 telah berjalan dan sesuai dengan amanat. Hal ini dibuktikan dengan adanya aspek-aspek pembiasaan yang menumbuhkan budi pekerti, dan terdapat beberapa kegiatan/ program yang menumbuhkan budi pekerti salah satu kegiatannya adalah Jumat Ceria, serta peran guru sudah terlihat dari apa yang telah guru lakukan.Kata kunci : budi pekerti, implementasi, peraturan menteri pendidikan dan kebudayaan